Productive performance, fertility and hatchability, blood indices and gut microbial load in laying quails as affected by two types of probiotic bacteria - Nour, Mohamed A.; El-Hindawy, Mohamed M.; Abou-Kassem, Diaa E.; Ashour, Elwy A.; Abd El-Hack, Mohamed E.; Mahgoub, Samir; Aboelenin, Salama M.; Soliman, Mohamed M.; El-Tarabily, Khaled A.; Abdel-Moneim, Abdel-Moneim E. (Saudi journal of biological sciences, 2021)
This study investigated two kinds of probiotic bacteria (Bacillus toyonensis, B1 and Bifidobacterium bifidum, B2) on laying Japanese quail’s performance, egg quality, fertility and hatchability, blood biochemical characteristics and microbiological parameters. A total of 270 mature quails (180 females and 90 males) were distributed into ten groups in a completely randomized design at eight weeks of age. The experimental groups were as follows: T1: basal diet only (control); T2-T5, basal diet plus 0.05, 0.075, 0.10 and 0.125% B1, respectively; T6: basal diet plus 0.10% B2; T7-T10: basal diet plus 0.05, 0.075, 0.10 and 0.125% B1 plus 0.05% B2, respectively. Results revealed that egg number (EN) and egg weight (EW) were gradually increased (P < 0.01) as the levels of both probiotic types increased. The feed conversion ratio (FCR) was significantly (P < 0.05) better within the total experimental period (8–20 weeks) due to B1 alone or/with B2 supplementation. Values of yolk percentage (Y%) were statistically (P < 0.01) higher only at 8–20 weeks of age and T10 recorded the highest value. By increasing the level of probiotics, fertility and hatchability percentages (F% and H%) were gradually increased (P < 0.01 and P < 0.05). Creatinine (CR) level was statistically reduced in birds fed T4 diet. Also, urea-N and aspartate aminotransferase (AST) levels were reduced in treated birds. The opposite was found regarding alkaline phosphatase (ALP). Conclusively, using B1 and B2 enhanced the productive performance, some egg quality traits, fertility and hatchability, digestive enzyme activities, and reduced the harmful bacteria in the gut of laying Japanese quail. Our findings could recommend to apply T4 (basal diet + 0.10 % B1), T6 (basal diet + 0.10% B2) and T9 (basal diet + 0.10% B1 + 0.05% B2) levels for the best results.